Primary orbital yolk sac tumor in an infant: A rare entity - Varsha Mishra; Sandeep Jain; Payal Malhotra; Garima Durga; Gauri Kapoor (Indian Journal of Pathology and Microbiology)
We report a case of pure orbital yolk sac tumor (YST) in an 11-month-old infant, which is a rare entity. The child presented with progressive painless swelling of the right eye and on examination had proptosis, chemosis, and lid edema. Systemic examination was within normal limits. Magnetic resonance imaging (MRI) orbit revealed a lobulated heterogeneously enhancing right retroocular mass extending up to the orbital apex, displacing the optic nerve and eroding the medial orbital wall. Biopsy of the lesion revealed pure YST histology. Serum alpha-fetoprotein (AFP) was markedly raised at 76900 ng/mL. She was started on infant bleomycin etoposide cisplatin (BEP) chemotherapy protocol. There was a good clinical and radiological response. A high index of malignancy is required in young children presenting with orbital proptosis. A multidisciplinary approach and early intervention are essential to save both vision and life.